2015
DOI: 10.1186/s40174-014-0027-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for the transition from work into retirement in Europe

Abstract: We use the labor force ad hoc module "transition from work into retirement" to analyze the link between individual as well as pension system characteristics and planned retirement age within the European Union. We find that timing of retirement is correlated between partners who are, already at the stage of retirement planning. In richer countries of the EU15, standard retirement age seems to have a larger effect on planned retirement age than in poorer EU15 states or in new EU member states. The effect of pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…In addition, higher education has been found to be related to better health at later age (Leopold and Engelhardt 2011), while the higher educated find better opportunities for employment and re-employment in their late careers (Schuring et al 2013). Henkens and Kalmijn's (2006) findings that workers in higher non-manual positions are less likely to exit early, and Riedel, Hofer and Wögerbauer's (2015) results that those employed in personal services plan later retirement, also fit this pattern.…”
Section: Entitlements Freedom Of Choice and Socio-economic Positionmentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, higher education has been found to be related to better health at later age (Leopold and Engelhardt 2011), while the higher educated find better opportunities for employment and re-employment in their late careers (Schuring et al 2013). Henkens and Kalmijn's (2006) findings that workers in higher non-manual positions are less likely to exit early, and Riedel, Hofer and Wögerbauer's (2015) results that those employed in personal services plan later retirement, also fit this pattern.…”
Section: Entitlements Freedom Of Choice and Socio-economic Positionmentioning
confidence: 83%
“…The size of the firm might matter, as larger companies often have had better coverage and enforcement of collective agreements which give better access to early retirement schemes (Naschold and De Vroom 1994). Riedel, Hofer and Wögerbauer (2015) found that employees in larger firms were more likely to at least plan for earlier retirement than those in smaller companies.…”
Section: Entitlements Freedom Of Choice and Socio-economic Positionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in most countries, net replacement rates in Germany will decline, possibly with positive effects on older workers' labour supply. For example, Riedel and Hofer (2013) refer to several studies showing positive effects of generous pensions on early retirement, whereas additional retirement effects from eligibility to occupational pensions and private pensions can be detected (Beier Sørensen 2014). Private pensions have spread relatively slowly in Germany, and other forms of savings currently yield low returns due to low interest rates and are mainly used by higher-status groups.…”
Section: Pension Generosity and Earnings-relatednessmentioning
confidence: 99%